A Review: Lantibiotics, a Promising Antimicrobial Agent - Basi-Chipalu, Shradha (Journal of Institute of Science and Technology, 2016)
Rise in multi drug resistant bacteria has been a public health problem. This has necessitated for the exploration of novel antimicrobials. Bacteriocins, probiotic bacteria, and bacteriophages are considered as alternatives to antibiotics. To this context, lantibiotics could be the future candidate for antimicrobial agent.Lantibiotics are synthesized ribosomally and after posttranslational modification active peptide is produced.Lantibiotics are lanthionine and methyllanthionine containing peptides exhibiting activity against multi drug resistant pathogens. Besides its application as alternatives to old antibiotics, they can be used as food preservatives, additives, probiotics, and prophylactics. Journal of Institute of Science and Technology Volume 21, Issue 1, August 2016, Page: 119-128